Mediação social e agroecologia: trajetórias e desafios dos agentes do Núcleo Missões da Rede Ecovida de Agroecologia - Cristina Bremm; Everton Lazzaretti Picolotto (Ciências Sociais Unisinos)
The process of modernization of the technical basis of agriculture has significantly changed the relationship of peasants whit their traditional way of practicing agriculture. From autonomous individuals they became subordinate to scientifically valid knowledge they have received from agronomists. Throughout the 1970s to 1990s, the social and environmental movements started to defend new forms of farming. In southern Brazil was created the Ecovida Agroecology Network as a discussion and articulation space on agroecology, guiding a new mode of relationship between farmers and technicians. Considering this context, the purpose of this article is to deal with complexity in social mediation relations involving ecological farmers, technicians and leaders linked to Missões Nucleus from Ecovida Agroecology Network, located in the northwest of Rio Grande do Sul state. This theme reveals its pertinence due to the large number of technicians and agronomists graduated in courses whose curricular degrees prioritize the study of conventional agriculture. The results of the study reveal that despite the mediators making efforts to reformulate their work practice and make it more dialogic and participatory in the interaction with the ecological farming families, there are asymmetries of power between the agents due to the cultural and symbolic capitals, habitus and different social insertions in agriculture.